Gender Equality and the Empowerment of Women and Girls Guidance for Development Partners (OECD Publishing, 2022)
Gender equality and the empowerment of women and girls are prerequisites to the realisation of the 2030 Agenda for Sustainable Development. This Guidance is a practical handbook for development partners supporting those global ambitions. Designed around the programme cycle and beyond, it provides practical steps for practitioners and examples of good practices, as well as checklists and recommendations on how to drive change